Acral persistent papular mucinosis: A case report and summary of 24 Japanese cases. Issue 10 (25th June 2021) - Mori, Asuka; Shinkuma, Satoru; Mitsui, Yasuhiro; Ogawa, Kohei; Miyagawa, Fumi; Asada, Hideo
Abstract: Acral persistent papular mucinosis is a rare subtype of localized lichen myxedematosus. We report a case of a 41‐year‐old woman with acral persistent papular mucinosis. She had a 5‐year history of multiple, scattered, whitish papules, on the back of both hands, of 2–5 mm in diameter. Histopathological examination revealed a focal, fairly circumscribed area with sparse collagen fibers in the upper and middle dermis. The circumscribed area was positively stained with Alcian blue. The papules were clinically and histologically diagnosed as acral persistent papular mucinosis. We also summarized 24 Japanese acral persistent papular mucinosis cases, including ours. Although acral persistent papular mucinosis occurs predominantly in women according to overseas reports, the male : female ratio is 5:7 in Japan. It has been reported that tranilast (N‐[3, 4‐dimethoxycinnamoyl]‐anthranilic acid) was effective in two Japanese cases. In our case, the patient had been treated with tranilast for 2 months without improvement. Further studies are required to confirm the efficacy of tranilast for acral persistent papular mucinosis.